Os feminismos e suas vozes: uma leitura junguiana das experiências de mulheres participantes de coletivos feministas - Lima, Raul Alves Barreto (2018)
Feminism emerged in the mid 19th century, was intensified in the 20th century and entered the 21st century as a multifaceted and highly active movement. Throughout its history, it has grown and pluralized, constructing new forms of knowledge, vindicating its ideas and ideals in several different ways. Nowadays, discussions on the topic have had a wider reach due to advances in technology that allow for new ways to disseminate its content. Feminism has provided a critical review of what it means to be a woman in the deepest and most complex sense of the term, pointing to particular ways of existing. Feminist practice has also constituted itself in collective spaces, representing an opening for sharing personal experiences, personal empowerment, and coordinating forms of action. With the aim of investigating the reasons that lead women to participate in these groups and to understand their experiences as feminists, the researchers conducted a qualitative study by administering semi-structured interviews to nine women who were participants in feminist collectives. Later, the narratives were categorized and organized in thematic groups and themes, analyzed according to analytical psychology and feminist literature. The results point to the transformative potential – both individual and collective – of feminist groups, pointing to the expansion of possibilities for being a woman and its multiple transformations. Women also expressed the importance of feminism as a space for personal empowerment, deconstruction and emancipation, which also shows the ongoing confrontation of conflicts inherent to the persona and shadow dynamics. Even though many challenges remain to be overcome, these women, imbued with heroic impulses, seek to achieve horizontal relationships based on respect for diversity, differences, and a commitment to oneself, others, and the world, in accordance with the dynamism of alterity. The participants were also sensitive to other forms of social injustice that did not directly affect them, such as racism and class prejudice. Based on this notion of internalized oppression, the results also help underpin the hypothesis of sexism as a cultural complex that is part of both the individual and collective psyche